Distinct amyloid-dependent patterns of nigra dopamine depletion in Lewy body diseases - Baik, Kyoungwon; Cha, Jungho; Park, Mincheol; Lee, Younggun; Chung, Seok Jong; Yoo, Han Soo; Sohn, Young H.; Lee, Phil Hyu (Frontiers in Aging Neuroscience, 2023)
Introduction Concomitant amyloid pathology is not uncommon and contributes to the clinical characteristics of Lewy body disease (LBD). We investigated the effect of amyloid on striatal18F-FP-CIT uptake patterns in LBD, including Parkinson's disease (PD) and dementia with Lewy bodies. Methods We enrolled 125 patients with LBD who underwent18F-florbetaben positron emission tomography (PET) and18F-FP-CIT PET. Patients were divided into amyloid-positive and amyloid-negative groups. We investigated the effect of amyloid on striatal dopamine transporter (DAT) availability, depending on the type of LBD, using general linear models with interaction analysis after controlling for age, sex, education, deep white matter hyperintensity (WMH), periventricular WMH, and cognitive status. Results There was a significant interaction effect between the disease group and the presence of amyloid on DAT availability in the anterior putamen, posterior putamen, caudate, and ventral striatum. In the presence of amyloid, only the PD group exhibited decreased DAT availability in the anterior and posterior putamen. In both groups, the presence of amyloid was not associated with DAT availability in the caudate and ventral striatum. The presence of amyloid was not directly related to the worse parkinsonian motor symptoms in both groups. However, there was a significant indirect effect of amyloid on parkinsonian motor symptoms, which was mediated by anterior and posterior putaminal DAT availability in the PD group alone. Discussion This study demonstrates different amyloid-dependent or amyloid-independent18F-FP-CIT PET patterns in patients with LBD, suggesting distinctive interactions between α-synuclein and amyloid pathology based on the type of LBD.